Management of Intrauterine Growth Retardation (IUGR) Through Ayurveda (AYUSHDHARA, 2025)
Food is the basic necessity for the human beings to survive and to carry out their daily activities. Diet varies from person to person, men and women and even based on the different age groups. Particularly in women, there is special dietary requirements during each stage of her life including childhood, adolescence, pregnancy, breast feeding and menopause. Specially during the pregnancy and breast-feeding nutrition of both and the foetus are very important as it is vital for both the mother and foetus to be healthy. Ayurveda lays great emphasis on ensuring holistic nutrition and even has a vast literature on the Pathya Apathya that needs to be followed according to the monthly regimen. It also elucidates in detail about the Garbhinicharya, Prasava and Sutikacharya etc regimen with more emphasis on the women health. Any deviation from the diet prescribed leads to various Garbhopadravas such as Garbhashosha, Upavisthaka, Nagodara etc. Intrauterine Growth Restriction (IUGR) is a main health condition affecting pregnant women and its outcomes are perinatal mortality and morbidity. This IUGR can be correlated to Garbhashosha in Ayurveda. The present study makes an attempt to review the researches that has been carried out on the condition Garbhashosha and to observe the effects of the same.